PEMANFAATAN FITUR CACTI BERBASIS TELEGRAM MESSENGER UNTUK NOTIFIKASI GANGGUAN JARINGAN DI PT. TELKOM AKSES MEDAN - Prida Apriani; Tengku Mohd Diansyah syah; Risko Liza (Universitas Harapan Medan, 2020)
Network monitoring helps to monitor and understand network problems that are happening so it can be handled as quickly as possible. CACTI is a network monitoring tools that monitors the network status when the network is up and down based on ping method and give a warning if a problem occurs in the network with an email form. However, the email function on CACTI has never been used by the engineer of PT Telkom Akses Medan due to the media coordination and communication that is being used on daily basic is Telegram Messenger. We need to install and analyze CACTI, designing the integration process of Telegram Messenger and handling fo notify network problems based on the operational area, to implement it with PHP and MySQL programs language by testing it with an exist device network. This final project create a CACTI function that able to notify a network problem through a notification from Telegram Messenger about the problem that occurs on the network with a dominance to deliver automatically and choosing each of the dynamic operational area.